2016
DOI: 10.5752/p.1678-9523.2015v21n2p272
|View full text |Cite
|
Sign up to set email alerts
|

Revisão sistemática de estudos sobre os aspectos escolares relacionados ao cometimento de delitos

Abstract: ResumoTrata-se de uma revisão sistemática da literatura nacional e internacional norteada pelo objetivo de investigar a relação entre escolarização e conduta infracional na adolescência. Foram consultadas duas bases de dados (Web of Science e LILACS) e a biblioteca Scielo, no período de 2009 a 2013. Os resultados oriundos da análise dos 25 artigos recuperados foram sintetizados em cinco categorias temáticas e evidenciaram a complexidade da interface existente entre os temas investigados, denotando a existência… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(43 reference statements)
0
2
0
4
Order By: Relevance
“…Such studies indicate that interventions are only benefi cial when they target the student's specifi c needs since conventional activities generally do not work out for this population. Various studies stress that increased schooling is a protective factor with respect to antisocial behavior (Casey, 2011;Gomide, Ropelato, & Alves, 2006;Matos, Martins, Jesus, & Viseu, 2015;Silva & Bazon, 2015;Silva, Cianfl one, & Bazon, 2016). In a meta-analysis of 18 studies concerning the role of prison education aimed at rehabilitating adult inmates, Ellison, Szifris, Horan, and Fox (2017) indicated that participating in educational activities reduces the probability of recidivism by approximately one-third, while producing a 24% increase in the inmate's likelihood of fi nding a job.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies indicate that interventions are only benefi cial when they target the student's specifi c needs since conventional activities generally do not work out for this population. Various studies stress that increased schooling is a protective factor with respect to antisocial behavior (Casey, 2011;Gomide, Ropelato, & Alves, 2006;Matos, Martins, Jesus, & Viseu, 2015;Silva & Bazon, 2015;Silva, Cianfl one, & Bazon, 2016). In a meta-analysis of 18 studies concerning the role of prison education aimed at rehabilitating adult inmates, Ellison, Szifris, Horan, and Fox (2017) indicated that participating in educational activities reduces the probability of recidivism by approximately one-third, while producing a 24% increase in the inmate's likelihood of fi nding a job.…”
Section: Discussionmentioning
confidence: 99%
“…Predominant among juvenile off enders, and especially those deprived of their freedom, defi ciency and failure have been considered risk factors for the development of antisocial behavior (Assis & Constantino, 2005;Bazon, Silva, & Ferrari, 2013;Dantas, 2014;Gallo & Williams, 2008;Lochner, 1999;Murray & Farrington, 2010;Nardi & Dell'Aglio, 2010;National Justice Council [CNJ], 2012;Padovani & Ristum, 2013;Sander et al, 2011). Silva and Bazon (2015) contended that the school signifi cantly infl uences the student's conduct -by way of its organizational structure, institutional atmosphere and practices -and they identifi ed poor performance, antagonistic relationships with peers and teachers, and frequent severe school punishments as factors that are associated with unlawful behavior. According to the above authors, poor performance could contribute to weakening the student's ties with the school, leading to his/her rejection and exclusion by peers and teachers.…”
mentioning
confidence: 99%
“…Foi realizada uma revisão sistemática de literatura, considerando artigos publicados nas bases de dados Eric, Lilacs, Pepsic, PsycInfo e Scielo. O período delimitado para a seleção de artigos foi de 2013 ao período em que foram realizadas as buscas (06 de fevereiro 2018), visando cobrir os estudos mais recentes e dar sequência a um trabalho que investigou esta temática até o período de 2013 (Silva & Bazon, 2015). Na realização das buscas, utilizou-se a combinação de quatro descritores nas línguas inglesa, portuguesa e espanhola: educação, escola, delinquência juvenil e adolescente em conflito com a lei, inseridos dois a dois, com o operador boleano "and".…”
Section: Métodounclassified
“…Alguns estudos indicam que um bom relacionamento do adolescente com os professores e colegas serve como base para fatores como vinculação e engajamento escolar, o que protegeria o adolescente do cometimento de atos infracionais. Esses fatores dificilmente estão presentes nas situações em que o adolescente vivencia reprovações ou punições severas no contexto escolar, pois as práticas punitivas afastam o adolescente da escola, assim esses podem ficar com tempo ocioso, aproximando-se de pares com comportamentos desviantes, o que contribui para a prática de atos infracionais (Silva & Bazon, 2015;Silva, Cianflone, & Bazon, 2016). Pereira e Sudbrack ( 2009) também argumentam que situações de reprovação e punições severas podem impactar de maneira negativa na autoestima e autoeficácia dos adolescentes, fazendo com que se sintam menos capazes de se adequar às regras impostas pela instituição escolar e de pertencer à comunidade escolar, afastando-os de projetos futuros relacionados à educação, o que lhes possibilitaria uma melhor inserção social.…”
Section: Infracionais Por Adolescentesunclassified
See 1 more Smart Citation